Climatology and annual cycle of global ocean dissolved oxygen represented by multiple observational gridded products - Juan Du; Lijing Cheng; Takamitsu Ito; Hernan E. Garcia; Zhankun Wang; Jonathan D. Sharp; Christopher J. Roach; Shoshiro Minobe; Yuntao Zhou; Bin Lu; Gian Giacomo Navarra; Seth M. Bushinsky (Ocean Science, 2026)
Ocean dissolved oxygen (O2) is an essential climate variable crucial for sustaining the marine life; thus, changes of O2 at various spatiotemporal scales should be quantified and understood. Here, we study the climatology and annual cycle of O2 at regional to global scales using eight available gridded observational products. These datasets are generated by different groups using different primary data selection, quality control, bias correction, and interpolation methods, including statistical and machine-learning-based mapping methods. A common set of metrics was collaboratively developed by the community of the Gridded Observational Dataset Intercomparison Project-Dissolved Oxygen (GODIP-DO) to facilitate the inter-comparison. We find that global mean O2 profiles are consistent among all products (±3 µmol kg−1), with the well-established decrease from high surface values to a minimum ∼ 1000 m, and subsequent increase to higher O2 at depth, although local differences could reach ±25 µmol kg−1 (0–1000 m). The hemispheric O2 annual cycle correlates strongly with ocean temperature changes, suggesting the key driver of temperature for the O2 annual cycle. However, there is substantial variation in the global mean 0–100 m O2 annual cycle, the magnitude ranges from −1 to 0.8 µmol kg−1, with a standard deviation of the datasets of ∼ 0.3 µmol kg−1. Average oxygen minimum zones (OMZ) volume among the products is 80.92 × 106 km3 (±1.95 %) for a 60 µmol kg−1 threshold and 152.00 × 106 km3 (±1.72 %) for a 90 µmol kg−1 threshold. Our results help to depict and understand the spread among the available O2 gridded datasets.